Synthetic lethal gene pairs: Experimental approaches and predictive models - Tang, Shan; Gökbağ, Birkan; Fan, Kunjie; Shao, Shuai; Huo, Yang; Wu, Xue; Cheng, Lijun; Li, Lang (Frontiers in Genetics, 2022)
Synthetic lethality (SL) occurs when the perturbation of either gene alone is viable but the simultaneous perturbation of both genes yields to the loss of viability. The key to exploiting synthetic lethal gene pairs in cancer treatment is to integrate experimental exploration in cancer biology and predictive modeling in computational biology. In this paper, we performed extensive review on experiment technologies, public data sources, and predictive models in studying synthetic lethal gene pairs. We recognize that SL prediction is broadly categorized into two approaches, individual cell line-based and population-based. We provide detailed descriptions of biological assumptions, experimental data, statistical models, and computation schemes of various SL predictive models, and speculate their influence on individual sample-based and population-based synthetic lethal interactions. At the end, we further discuss the pros and cons of existing SL data and models, and point out the potential future research directions in SL discovery.